1996
DOI: 10.1007/bf00311768
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of results of surgery performed over a 20-year period on 500 patients with cancer of the thoracic esophagus

Abstract: This study was conducted to examine the long-term outcome of 500 patients who underwent surgery for cancer of the thoracic esophagus during the past 20 years. Favorable results were obtained with postoperative adjuvant radiation and chemotherapy and there were no surgical deaths in the last 5 years. The mortality rate decreased from 17% prior to 1980 to 5% between 1981 and 1993, this being most probably attributable to the decreased incidence of suture leakage. With respect to changes in surgical techniques, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 1 publication
0
31
0
Order By: Relevance
“…Our standard operative procedure is right transthoracic esophagectomy and resection of the lesser curvature with dissection of the mediastinal (involving the periesophageal region and areas around trachea and bilateral main bronchus) and the abdominal (involving the perigastric region and areas around the celiac axis) lymph nodes [1,10,11] . For upper thoracic esophageal cancer, or when metastases involve neck and/or upper mediastinal lymph nodes, we add bilateral neck dissection and perform a so-called three-field lymph node dissection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our standard operative procedure is right transthoracic esophagectomy and resection of the lesser curvature with dissection of the mediastinal (involving the periesophageal region and areas around trachea and bilateral main bronchus) and the abdominal (involving the perigastric region and areas around the celiac axis) lymph nodes [1,10,11] . For upper thoracic esophageal cancer, or when metastases involve neck and/or upper mediastinal lymph nodes, we add bilateral neck dissection and perform a so-called three-field lymph node dissection.…”
Section: Methodsmentioning
confidence: 99%
“…Esophagectomy with extensive lymph node dissection for thoracic esophageal cancer is one of the most invasive surgical procedures and continues to be associated with high a morbidity, despite improvements in the surgical techniques [1,2] . It is associated, for instance, with severe hemodynamic changes involving loss of circulating blood volume and filling of the third space during the immediate postoperative period.…”
Section: Introductionmentioning
confidence: 99%
“…Different methods have been used to predict anastomotic leak, including the measurement of haemostatic markers, 225,309 the assessment of the blood supply and tissue oxygen tension (PtO 2 ) perioperatively 225,231,[309][310][311] and the quantification of various factors in drainage secretions.…”
Section: Box 25 Literature On the Prediction Of Anastomotic Leakmentioning
confidence: 99%
“…Abo and co-workers 310 implanted sensors at the anastomotic site in patients undergoing reconstructive surgery of thoracic oesophageal cancer to measure blood and PtO 2 levels, and found that oxygen levels varied significantly in the presence of suture leakage. Schilling and co-workers 231 conducted a similar uncontrolled, observation study to measure gastric perfusion before, during and after gastric tube formation in patients undergoing thoracic oesophagectomy.…”
Section: Tissue Oxygen Tensionmentioning
confidence: 99%
“…The posterolateral thoracotomy incision is then closed. Thereafter, with the patient in a supine position, esophageal reconstruction is done using gastric tube or colon tissue via the subcutaneous or retrosternal route [3,4] .…”
Section: Techniquementioning
confidence: 99%